KEHILANGAN BIOMASSA GAMBUT AKIBAT KEBAKARAN HUTAN - Wiri, .; Astiani, Dwi; Fernando, Togar (Universitas Tanjungpura, 2017)
Peat land is a wetland / water-saturated area composed of organic soil material, namely the remains of plants and plant tissue decaying with a thickness of more than 50cm comprising organic materials, either with a thickness of more than 45cm or layered together with mineral soil with thickness of 80cm and have a thick layer of organic material is more than 50cm. Peat serves as a repository of highest carbon reserve after a very large tree. Additionally peat has a role in the ecosystem of peatlands both in terms of hydrology, conservation of wildlife and vegetation. Kuala Dua Village in Kubu Raya has a fairly extensive peatlands with a depth of 1-4 meters. Fire is a phenomenon that often occurs in Kuala Dua Village including peat fires. The fires emit carbon that contribute to the increase of greenhouse gases (GHGs) into the atmosphere. So there is a need to do research on